Urban Trees and Allergies in North Florida - Jennifer A. Seitz; Francisco Escobedo (EDIS, 2009)
FOR-206, a 4-page fact sheet by Jennifer A. Seitz and Francisco Escobedo, explains tree pollen production, allergenicity ratings, and strategies to reduce pollen exposure. Includes references and a table listing 15 commonly used native trees and their OPALS ratings. Published by the UF School of Forest Resources and Conservation, February 2009.